Pelarangan LGBT Ditinjau dalam Perspektif Pembatasan Hak Asasi Manusia - M. Zulkarnain Firmansyah; Erny Herlin Setyorini (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study examines the prohibition of lesbian, gay, bisexual, and transgender (LGBT) practices from the perspective of Human Rights. The background of this research is based on the LGBT phenomenon, which is perceived as conflicting with moral values, religious norms, and public order in Indonesia, as regulated in Article 28J paragraph (2) of the 1945 Constitution of the Republic of Indonesia. This provision allows for the limitation of human rights in order to safeguard security and public interests. The research employs a normative juridical method with statutory and conceptual approaches. The findings indicate that within the framework of human rights, there are rights that may be limited or reduced (derogable rights). The prohibition of LGBT practices is categorized as a form of limitation of human rights that falls under derogable rights and does not constitute non-derogable rights, which are rights that cannot be restricted under any circumstances, such as the right to be free from torture, the right to life, and the right to freedom of religion. Furthermore, the prohibition of LGBT practices within the military environment is considered legitimate insofar as it remains within the limits of human rights, given that the military possesses distinctive characteristics and discipline that are deemed incompatible with LGBT practices. However, the criminalization of LGBT actors within the military context still requires more explicit criminal law regulations to prevent legal disparities and to ensure that the principles of non-discrimination and equality before the law are upheld.